The Impact of Strategic Entrepreneurship on Strategic Performance: An Analytical Study at Maysan Oil Company - Challoob Hashim, Maytham; Chaouachi, Slim; Bchini, Belgacem; Flayyih, Hakeem Hammood (Journal of Economics and Administrative Sciences, 2024)
Purpose: This research collects essential variables in the cognitive level of Strategic Management Resources (SMR) and provides a theoretical framework for Strategic Entrepreneurship (SE) and Strategic Performance (SP), which may benefit other researchers.Theoretical framework: Organizations seek an in-depth study to discover the reasons for developing SE and its impact on SP in encouraging employees to work or adapt to the new society. This study explores the impact of SE on SP at Maysan Oil Company.Methodology: The descriptive analytical method was used in this research to study and analyze phenomena due to its flexibility. Maysan Oil Company was chosen as a sample for the study due to the availability of human talents. A purposive random sampling method was used for the opinions of administrative leaders, where 305questionnaires were distributed and 300 retrieved.Results: The research results constitute an excellent path toward the impact of SE on SP within the company and provide scientific evidence for administrative leaders to achieve SE for the company and improve the level of SP, which strengthens the position of Maysan Oil Company compared to oil companies.Research, Practical & Social implications: The research results emphasize the importance of achieving competitive advantage and outstanding performance that enhances SE in Iraqi oil companies.Originality/value: The research value comes from studying the relationship between the research variables in the study environment, as this relationship has yet to be investigated in most Iraqi institutions in general.